The influence of organizational climate dimensions on employee involvement with the quality management system: an exploratory study - Nik Abdullah, Nik Azlina; Nik Abdul Rashid, Nik Ramli; Anwar, Nur Aizureen (2011)
As one of the nation leading university, UiTM commitment to Quality Management System (QMS) is absolutely unquestionable and its implementation has been right from its establishment and has been growing ever stronger until this present day and definitely through its future years. Knowing that the success of any QMS initiative will depend on its employee involvement, identifying the antecedents to this behavioral attributes is thus crucial. This study has successfully identified 7 organizational climate dimensions that would contribute to employee involvement to the quality management initiative. These OC dimensions are integration, supervisory support, effort, feedback, quality, flexible and formalization. The multiple regression model resulted in the adjusted R2 of 0.61 is considerably high (61 % predictive ability). The most significant dimension is feedback (8=0.280), followed by quality (8=0.233), flexible (8=0.196), integration (8=0.84), formalization (8=-0.157), supervisory support (8=0.136) and lastly effort (8=0.127). To ensure high employee involvement with the QMS initiative, management need to put in place an effective and immediate employee feedback mechanism. Though important, supervisory support rank least significant of the DC dimensions, showing that they are just to provide direction and authority, whilst the employee commitment to quality management has to be intrinsic. Another very interesting outcome is that, while all other dimensions of OC have positive relationship to employee involvement, formalization has a negative relationship. Higher employee involvement is the outcome of lower bureaucracy. For the quality management to be successful, participant need to have freedom to work beyond formal limits, as this is the bedrock of innovative and creative behavior. An important element embedded in quality management system is continuous improvement (kaizen). An organization to entrench in birocracy will restrict innovative culture among its employees. Descriptive statistics is another important aspect of this study. It gives a snapshot of what is going on in an organization. Employee involvement and all dimensions of DC have only moderate score on the Likert scale (1 =strongly disagree to 5=strongly agree). None of the variable has a means score of more than 4. The respective mean score for the entire variable are; Involvement (2.80), quality (3.33), formalization (3.15), integration (2.87), supervisory support (2.84), feedback (2.83) and flexible (2.63). Management has to see this situation as a challenge for further increase their effort to ensure stronger employee involvement and more pro "quality management climate" in the organization.